2014
DOI: 10.1155/2014/628604
|View full text |Cite
|
Sign up to set email alerts
|

Surface Protection of Carbon Steel by Hexanesulphonic Acid-Zinc Ion System

Abstract: Inhibition of corrosion of carbon steel in dam water by hexanesulphonic acid as its sodium salt C6H13SO3Na (SHXS) in the absence and presence of a bivalent cation zinc ion (Zn2þ) has been investigated using weight loss method. Results of weight loss method indicate that inhibition efficiency (IE) increased with increase of inhibitor concentration. Polarization study reveals that SHXS-Zn2+ system controls the cathodic reaction predominantly. AC impedance spectra reveal that a protective film is formed on the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…To explore the effect of LFH on the initiation and development of corrosion at the Cu/solution interface, (AFM) has emerged as a promising new method (Anbarasi et al, 2012;Sherine et al, 2010;Singh et al, 2011;Wang et al, 2011). AFM image analysis was used to determine the root mean square surface roughness (Sq) and mean roughness (Sa) for copper surfaces immersed in different environments.…”
Section: Eis Measurementsmentioning
confidence: 99%
“…To explore the effect of LFH on the initiation and development of corrosion at the Cu/solution interface, (AFM) has emerged as a promising new method (Anbarasi et al, 2012;Sherine et al, 2010;Singh et al, 2011;Wang et al, 2011). AFM image analysis was used to determine the root mean square surface roughness (Sq) and mean roughness (Sa) for copper surfaces immersed in different environments.…”
Section: Eis Measurementsmentioning
confidence: 99%
“…To analyze the influence of inhibitor on the surface morphology of the metal surface, AFM was used [28]. The morphology and the cross-sectional profile for polished carbon steel surface, corroded bare metal, and the carbon steel surface coated with lignin are shown in Figs.…”
Section: Atomic Force Microscopy (Afm)mentioning
confidence: 99%
“…of a condensation protective film on the carbon steel surface, which is responsible for inhibiting corrosion. It can be shown that the surface coverage increases, which in turn leads to the formation of an insoluble compound on the surface of the metal (Fe 2+ -CPHAQ2O complex), and the surface is covered with a thin layer of inhibitors that control the dissolution of solid carbon [19][20][21].…”
Section: /T (K -1 )mentioning
confidence: 99%